Pengembangan Jejaring Wirausaha dan Pembelajaran Eksploratif Sebagai Upaya Meningkatkan Kinerja Perekonomian Unit Usaha Kecil Menengah di Semarang - Enny Susilowati M; Guruh Taufan (Semantik, 2013)
The research examines the effect  Network of Entrepreneurial which measured by  social  networking,  networking  support, networking among firms and Explorative Learning toward Performance Unit Small and Medium Enterprises in Semarang.This research use sample consisted of  100  Unit Small and Medium Enterprises    in Semarang.  The data  are taken from central statistical agency of Semarang.  Selection of samples by using purposive sampling.  The hypothesis testing model using Partial Least Square analysis (PLS.    The result of the research indicated, the  Network of Entrepreneurial  and Explorative Learning are factors that  affect positively on  Performance Unit Small and Medium Enterprises  .  The positive result in  Network of Entrepreneurial and Explorative Learning gives the impact for Unit Small and Medium Enterprises in Indonesia to more focus Network of  Entrepreneurial  Development Model.  These findings  contribute  that  entrepreneurial  networking  should  be astrategic  priority  for every company.  Linkages  with suppliers  to  increase the  resources  of the  market  development,  new technologies  and competitors  movement  and  access to  business  partners,  sources of  technical  assistance  from customer ideas. With the existence of  a positive  relationship  between  Entrepreneurial  Networking  and  Explorative  Learning  is a key factor  in developing  the dissemination of knowledge  and  learning  that  will  increase  competitive  advantage  and  improve  the performance of SMEs.